The Relationship Between Hemodialysis Frequency and the Tendency of Depressive Symptoms Among Dialysis Patients - Jessica Maria Karminda Maheswari; Teguh Dwi Nugroho; Deif Tunggal; Efrisca Meliyuita Br Damanik (Utan Kayu Publishing, 2025)
Background: Patients undergoing hemodialysis often experience both physical and psychological impacts. This study aimed to determine the relationship between hemodialysis frequency and the tendency of depressive symptoms. Methods: This was a cross-sectional study conducted at three hospitals in Kupang City: Siloam Hospital Kupang, Prof. W.Z. Yohanes Regional Hospital, and dr. Ben Mboi Central Hospital. Research variables included hemodialysis frequency and the tendency of depressive symptoms. Data were collected using the BDI-II questionnaire through interviews or self-administration. Statistical analysis was performed using Spearman’s correlation with a 95% confidence level. Results: Among 163 respondents, 5 (3.1%) had a low frequency, 140 (85.9%) had a moderate frequency, and 18 (11%) had a high frequency. A total of 101 patients (62%) were categorized as normal, 28 (17.5%) had mild depression, 22 (13.5%) moderate depression, and 12 (7.4%) severe depression. Statistical analysis revealed no significant relationship between hemodialysis frequency and depressive symptom tendency (p = 0.491 0.05). Conclusion: Although many hemodialysis patients experienced depressive symptoms, statistical analysis did not show a significant association between hemodialysis frequency and the tendency of depressive symptoms. Further studies are needed to explore other factors influencing depression in this population.